Management Audit of Purchasing Function on the 1st Semester of 2020 in Jimbaran Bay Beach Resort & Spa Hotel - Ni Putu Trisnawati; IK Sukayasa; IM Suarta (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
This research aims to determine whether management audit can detect weaknesses that occur in the purchasing function at the Jimbaran Bay Beach Resort & Spa Hotel and provide recommendations for these weaknesses. This research uses descriptive qualitative methods, namely the stages of management audit. The results of the management audit of the purchase function showed that there are weaknesses such as the price of goods not following the purchase order (PO), the supplier does not send the goods under the purchase order (PO), late payment of the debt to the supplier, the process of releasing goods without store requisition (SR), and the difference in the number of items in the store physically with the visual hotel program (VHP) system. The recommendations regarding to these weaknesses are by (1) selecting suppliers that/which are fit to the required criteria, and (2) do not just choose more than one supplier, (3) conduct meetings with suppliers regularly, and (4) tighten in releasing goods in stores.